Using Fondi Application to Escalate the Speaking Ability of EFL High School Students - Rambe, Ifrah Hayani; Amran, Ali (Universitas Pahlawan Tuanku Tambusai, 2024)
Gamification in learning introduces a new atmosphere for students learning English. Application-based learning offers accessibility and flexibility for users. This study aims to understand students’ perceptions of the Fondi application and explore its effectiveness in enhancing English speaking skills. The research employs a case study method at MAN 1 Medan, using data collection techniques such as observation, interviews, and documentation. Data analysis follows Miles and Huberman’s approach, which includes data reduction, data presentation, and conclusion drawing. The study’s informants are 11th-grade students using the Fondi application and English teachers. The findings indicate that students at MAN 1 Medan have positive perceptions of the Fondi application, feeling more motivated and confident in practicing English speaking. The gamification features of the application, such as challenges, points, and levels, have proven effective in increasing student engagement and English-speaking abilities. Additionally, the competition and collaboration elements within the Fondi application strengthen social interaction among students, providing an authentic and contextual learning experience. The author recommends that future researchers study the use of the Fondi application in various educational contexts with more diverse samples and longer research durations. Further research should also collect longitudinal data to observe the long-term impact of using this application.